Taxonomic studies on Amomum (Zingiberaceae) in China V: Amomum arunachalense var. allioides, a new variety from Xizang - Wang, Qing-Long; Yuan, Lang-Xing; Dong, Shu-Peng; Tang, Huan; Yang, Hu-Biao; Ye, Xing-Er (Phytotaxa, 2026)
Amomum arunachalense var. allioides (Zingiberaceae: Alpinioideae), a new variety from Medog County of Xizang, China is described and illustrated here. This variety mainly differs from A. arunachalense in having green to pale yellow fruits. Other minor differences include larger lamina, bifid or lacerate ligule, shorter peduncle, and indumentum on scales, calyx and filament. We provide a colour plate as well as comprehensive information regarding the habitat, ecology, phenology and IUCN conservation assessment for this new variety.